Investment Policy Analysis Between Generation Z and Millennial Generation - Fadali Rahman; Aditya Iskandar Syah; aisyah, Aisyah Safitri; ayu, Ayu Maulidia; subhan, subhan (Yayasan Kita Menulis, 2026)
This study aims to analyze and This study uses a quantitative approach with a comparative associative survey method and involves 100 respondents (50 Gen Z and 50 Millennials) who are domiciled in Indonesia and have investment experience, with a purposive sampling technique . comparing investment policies between Generation Z and Millennials in Indonesia. These two demographic groups are